FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KETEPATAN PEMBERIAN MAKANAN PENDAMPING ASI (MP-ASI) PADA BAYI USIA 6- 12 BULAN DI WILAYAH KERJA PUSKESMAS TAMBU KECAMATAN BALAESANG KABUPATEN DONGGALA - raihan, aminudin (Husada Mahakam, 2016)
Giving Complementary feeding (MP-ASI) is a reliable means to establish a Human Resources (HR) quality. However, there are many mothers who have difficulty in providing breast milk for her baby. The culture of the community that feeds bananas to infants before 6 months of age. It is very dangerous for infants because of its digestive not ready to receive food other than breast milk. The purpose of this research is knowing the factors associated with the accuracy of feeding companion action (MP-ASI) in infants aged 6 -12 months in Puskesmas Tambu Balaesang District of Donggala. This type of research is an analytic study with cross sectional design population in this research is all mothers with babies aged 6-12 months as many as 119 people. The sample size is calculated using the formula Slovin is numbered, 54 people. The sampling technique is done by proportional random sampling. The data analysis is done of univariate and bivariate using Chi-square test. The result showed mothers aged ≥ 25 years (66.7%). Low education (51.9%), a mother with a good knowledge about the provision of complementary feeding (51.9%), good attitude about the MP-ASI (75.9%), low motivation in providing breast milk (61.1% ), giving breast milk is not appropriate (53.7%), results of the statistical test Chi Square age p-value = 0.005, p = 0.003 education, knowledge of the value of p = 0.000, p = 0.004 attitudes and motivational value of p = 0.000. The conclusion of the research is no correlation between age, education, knowledge, attitudes and motivation of mothers with precision giving complementary feeding in infants aged 6-12 months. Advice for health center staff Tambu Balaesang District of Donggala so routinely providing information on complementary feeding (MP-ASI) so that the mothers can provide complementary feeding (MP-ASI) is appropriate.